A Pre-Interventional Scale to Predict in situ Atherosclerotic Thrombosis in Acute Vertebrobasilar Artery Occlusion Patients - Zha, Mingming; Wu, Min; Huang, Xianjun; Zhang, Xiaohao; Huang, Kangmo; Yang, Qingwen; Cai, Haodi; Ji, Yachen; Lv, Qiushi; Yang, Dong; Dai, Qiliang; Liu, Rui; et al. (Frontiers in Neurology, 2021)
Background and Purpose: Determining the occlusion mechanism before endovascular treatment (EVT) is of great significance for acute large vessel occlusion patients. We aimed to develop and validate a simple pre-EVT scale with readily available variables for predicting in situ atherosclerotic thrombosis (ISAT) in acute vertebrobasilar artery occlusion (VBAO) patients. Materials and Methods: Consecutive patients were retrieved from Nanjing Stroke Registry Program between January 2014 and December 2019 as a derivation cohort. Anonymous data of consecutive patients between January 2014 and December 2019 were collected from another comprehensive stroke center as an external validation cohort. Demographics, medical histories, and clinical characteristics were collected. ISAT was defined according to the following criteria: (a) detection of moderate to severe (≥50%) stenosis or stenosis with significant distal flow impairment at the occluded segment when successful reperfusion was achieved; (b) transient visualization of eccentric plaque contour or a recurrent re-occlusion tendency when reperfusion was unsuccessful. Logistic regression was taken to develop a predictive scale. The performance of the scale was assessed by area under the receiver operating characteristic curve (AUC) and Hosmer–Lemeshow test. Results: ISAT was observed in 41 of 95 (43.2%) patients included in the derivation cohort. The ISAT predictive scale consisted of three pre-interventional predictors, including the history of hypertension, atrial fibrillation rhythm, and baseline serum glucose level ≥7.55 mmol/L. The model depicted acceptable calibration (Hosmer–Lemeshow test, P = 0.554) and good discrimination (AUC, 0.853; 95% confidence interval, 0.775–0.930). The optimal cutoff value of the ISAT scale was 1 point with 95.1% sensitivity, 64.8% specificity, and 77.9% accuracy. In the validation cohort, the discrimination ability was still promising with an AUC value of 0.800 (0.682–0.918). Conclusion: The three-item scale comprised of the history of hypertension, atrial fibrillation rhythm, and dichotomous serum glucose level had a promising predictive value for ISAT before EVT in acute VBAO patients.